Political Economy of Subsidized Fuel Control: Assessing Indonesia's Technological Approach and Potential Savings - Wibowo, Muhammad Ridzki; Abdullah, Imaduddin (The Indonesian Forestry Certification Cooperation, 2023)
This study analyzes the potential of Indonesia's technological approach to control subsidized fuels. To achieve its objective, the study employs both quantitative and qualitative analyses. Quantitatively, the research seeks to estimate the potential value of inefficiently targeted fuel subsidies and assess the potential fiscal savings achievable through diverse fuel restriction measures. In this case, the study carried out four simulations to assess the impact of fuel consumption controls. Meanwhile, the qualitative analysis aims to delve into details of Indonesia's technological infrastructure used to control the consumption of subsidized fuels. Furthermore, the study investigates the key challenges and successes associated with Indonesia's technological approach to control subsidized fuels. This study contributes insights into achieving fairness in fuel regulatory policies while calculating fiscal savings and the potential of technology-driven solutions. While promising, ongoing challenges of MyPertamina necessitate further improvements for optimal functionality in assignment fuels (JBKP) distribution. This research informs discussions on equitable and technologically-driven energy policy solutions in the context of achieving global climate goals and local economic dynamics.